The moderating effect of youth sports coaches' identities on their professional knowledge orientations: a social network perspective - Liraz, R.; Eyal, O. (International Sport Coaching Journal, 2026)
The present study used social network analysis to investigate the moderating effect of individuals` identities on the relationship between the structure of their networks and professional knowledge orientations (exploitation, exploration, and ambidexterity). It examined the ego networks of Israeli youth soccer coaches (N = 88) based on their vocational and personal sources of knowledge, including sportive, personal development, and friendship networks. The findings indicate that youth soccer coaches` sportive identity embeddedness enhances their knowledge exploitation even when they have access to nonredundant, new, and versatile knowledge. But in the case of lower levels of athlete identity and nonredundant versatile networks, youth soccer coaches display ambidexterity by exploring novelty while relying on their familiar past knowledge and routines. Overall, the study describes the challenges of a single salient identity and points out the importance of cultivating diverse networks and multiple identities to facilitate effective and sustainable knowledge acquisition and utilisation for long-term professional advancement.